2012
DOI: 10.1111/j.1600-0668.2012.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Residential indoor PM2.5in wood stove homes: follow-up of the Libby changeout program

Abstract: In 2005 through 2008 a small rural mountain valley community engaged in a wood stove changeout program to address concerns of poor ambient air quality. During this program we assessed changes to indoor air quality before and after the introduction of a new, lower emission wood stove. We previously reported a greater than 70% reduction in indoor PM2.5 concentrations in homes following the installation of a new EPA-certified stove within the home. We report here on follow-up of the experiences in these and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 29 publications
6
81
0
Order By: Relevance
“…Previous studies in developed countries, conducted mostly in rural areas, have shown wood stove use to be an important source of indoor PM 2.5 (particulate matter with aerodynamic diameter < 2.5 μm) [2–7]. Further, studies of wood stove exchange programs in rural regions of the United States have suggested that improvements in stove design may lead to reductions in both indoor and outdoor PM 2.5 levels [812]. There are few data in urban areas in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in developed countries, conducted mostly in rural areas, have shown wood stove use to be an important source of indoor PM 2.5 (particulate matter with aerodynamic diameter < 2.5 μm) [2–7]. Further, studies of wood stove exchange programs in rural regions of the United States have suggested that improvements in stove design may lead to reductions in both indoor and outdoor PM 2.5 levels [812]. There are few data in urban areas in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the amount of wood-smoke particles in an area is highly dependent on the relative number of wood-fueled residential combustion appliances, the frequency of use, and the burn rate, as well as wood species, wood quality, 43---45 and wood stove operation. 46,47 The lack of data on factors related to the combustion type, activity, and conditions, and our inability to adjust for these household-level potential confounders in our analyses, may at least partially explain results that were not statistically significant. However, these issues could not be explored further because of the ecological design of this study.…”
Section: Discussionmentioning
confidence: 53%
“…PM2.5 did not decrease after the intervention; however, our measurement periods were only a few days out of the 1-year post-intervention period. Although early woodstove interventions showed decreases in PM2.5, more recent wood change-out studies have had variable results with many houses not demonstrating significant sustained PM2.5 decreases [25,26]. The varied PM2.5 response across homes in our studies and others may be due to factors (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…The varied PM2.5 response across homes in our studies and others may be due to factors (e.g. household size, household activities, ventilation) other than the introduction of a new woodstove [25,27]. The recent Asthma Randomized Trial of Indoor Wood Smoke study demonstrated that air filtration units were superior (68% decrease) to woodstove change-out (no significant reductions) in reducing PM2.5 in homes; however, their effectiveness in reducing LRTIs is unknown [28].…”
Section: Discussionmentioning
confidence: 99%